Review of the Minister of Manpower's Circular Letter Number M/5/HK.04.00/V/2025 in Providing Legal Justice for Workers - Vivienne Olivia Siswanto; Moody Rizqy Syailendra (Jurnal Daulat Hukum, 2025)
The practice of withholding diplomas often leads to injustice and inequality in workers' positions because diplomas are personal documents that serve as symbols of academic achievement as well as tools for obtaining employment. Therefore, the government issued Circular Letter of the Minister of Manpower Number M/5/HK.04.00/V/2025 as a form of protection for workers from abuse of authority by employers. This study aims to examine the extent to which this circular letter is able to provide legal justice and certainty in the implementation of industrial relations. The method used is normative legal research with a qualitative approach, through a review of laws and regulations, doctrines, and related legal literature. The results of the analysis indicate that this circular serves as an ethical and administrative guideline that strengthens the position of workers, but does not yet have binding legal force because it is not included in the hierarchy of laws and regulations. Therefore, the establishment of stricter regulations at the statutory level is needed to ensure balanced protection between workers and employers. This research is expected to contribute to the reform of labor law so that the principle of substantive justice between workers and employers can be realized